Structural diversity, magnetic property, or luminescence sensing of Co(ii) and Cd(ii) coordination polymers derived from designed 3, 3′-((5-carboxy-1, 3-phenylene)bis(oxy))dibenzoic acid. Issue 27 (13th June 2019) - Yang, Dong-Dong; Lu, Li-Ping; Zhu, Miao-Li
Abstract : Three Co(ii )-CPs and two Cd(ii )-CPs were synthesized and the Cd(ii )-CPs can detect CrO4 2− and Cr2 O7 2− anions in aqueous solution. Abstract : Five novel coordination polymers (CPs), formulated as [Co3 (μ4 -cpboda)2 (μ1, 1 -OH2 )2 (2, 2-bipy)2 ]·1.5DMF·2H2 O n (1 ), [Co3 (μ3 -cpboda)2 (4, 4′-bpy)3 (H2 O)2 ]·4H2 O n (2 ), [Co(μ2 -H2 cpboda)2 (1, 4-bib)3 (H2 O)2 ]·H2 O·DMF·1.5HCOOH n (3 ), [Cd(μ3 -Hcpboda)(1, 4-bib)] n (4 ), and [Cd3 (μ4 -cpboda)2 (μ1, 1 -OH2 )2 (phen)2 ]·2DMF·1.5H2 O n (5 ) (H3 cpboda = 3, 3′-((5-carboxy-1, 3-phenylene)bis(oxy))dibenzoic acid, 2, 2-bipy = 2, 2-bipyridine, 4, 4′-bpy = 4, 4′-bipyridine, 1, 4-bib = 1, 4-di(1 H -imidazol-1-yl)benzene, phen = 1, 10-phenanthroline) have been synthesized under solvothermal conditions and characterized by elemental analyses (EAs), single-crystal X-ray diffraction analyses, X-ray powder diffraction analyses (PXRD), FT-IR spectra, and thermogravimetric analyses (TGAs). The structural analyses reveal that these complexes have four 2D coordinate polymers and one 3D framework, in which metal ions are in octahedral coordination geometries in1–3 and5, but seven-coordinated disordered pentagonal bipyramids in4 . Complexes1 and5 represent linear trinuclear [M3 (μ1, 1 -OH2 )2 (μ1, 3 -COO)4 ] SBUs in1 (M = Co(ii )) and in5 (M = Cd(ii )) based on a 3, 4, 6-connected net with a point symbol (3 2 ·4)2 (3 2 ·8 3 ·9)2 (3 4 ·4 2 ·8 2 ·9 4 ·10 3 ) net, complex2 exhibiting a (3-c)2 (4-c)(4-c)2 3D structure with the (5 2 ·6·8 2 ·9)2 (5 2 ·6 2 ·9 2 )(5 2 ·6)2 topology and complexes3 and4 having a novel 2D framework with the point symbol of (4 4 ·6 2 ). Magnetization analyses disclose the antiferromagnetic (AF) behaviors between Co(ii ) ions in complexes1 &3 and S = 3/2 (Co 2+ ) spin Heisenberg chains with alternating magnetic sequences (F/F/AF) n in2 . Fluorescence measurements indicate that4 and5 are promising luminescence sensors for the detection of CrO4 2− and Cr2 O7 2− anions in aqueous solution.